The Difference of Sagittal Correction of Adult Subaxial Cervical Spine Surgery According to Age: A Retrospective Study. Issue 8 (12th July 2022) - Wu, Jionglin; Guo, Rui; Yang, Canchun; Yan, Haolin; Wang, Zheyu; Chen, Zhipeng; Peng, Xiaoshuai; Zhang, Di; Jiang, Xu; Zhao, Qiancheng; Li, Bo; Hu, Xumin; et al.
Abstract : Objective: At present, the true sagittal alignment of the cervical spine is uncertain, resulting in no standard reference for subaxial cervical surgery. So, we aimed to explore the age difference of normal cervical sagittal alignment and to further investigate the mid‐and long‐term changes of sagittal alignment after subaxial cervical spine surgery. Materials and Methods: This was a retrospective study and 1223 asymptomatic volunteers and 79 patients undergoing subaxial cervical spine surgery were retrospectively reviewed in total. Asymptomatic volunteers and patients were divided into six subgroups: 20–29, 30–39, 40–49, 50–59, 60–69 and ≥70 groups. The age difference and trend with age of cervical sagittal parameters of asymptomatic volunteers were assessed by cervical lateral radiography and analyzed by ANOVA test, and the regression equation of C2‐7 Cobb was established via multiple linear regression. Based on the C2‐7 Cobb regression equations of different ages, the theoretical value, deviation value, loss value of the C2‐7 Cobb, and JOA recovery rate of patients were calculated, and the correlation among the loss value, deviation value of the C2‐7 Cobb, and JOA recovery rate of the 79 patients was evaluated by Pearson correlation analysis. Results: For the asymptomatic volunteers, the C0‐2 Cobb decreased gradually with increasing age. The C2‐7 Cobb, C2‐7 SVA, T1S, NT, and TIA increased gradually with increasing age. The CBVA fluctuated with increasing age. T1S demonstrated a moderate correlation with C2‐7 Cobb ( r  = 0.60, p  < 0.01); C0‐2 Cobb, C2‐7 SVA, CBVA, and TIA demonstrated a fair correlation with C2‐7 Cobb ( r  = −0.30, −0.33, 0.41, 0.40, p  < 0.01); age demonstrated a poor correlation with C2‐7 Cobb ( r  = 0.19, p  < 0.01). The regression equations of C2‐7 Cobb were established using C0‐2 Cobb, C2‐7 SVA, CBVA, and T1S. For the patients with subaxial cervical spine surgery, the loss of C2‐7 Cobb was moderately correlated with the deviation of C2‐7 Cobb ( r  = 0.33, p  < 0.01). Conclusion: The age difference of cervical sagittal alignment was obvious, and the C2‐7 Cobb increased with age especially. The closer the postoperative C2‐7 Cobb was to the theoretical value of corresponding age, the smaller the loss of correction angle was, and the better the mid‐ and long‐term outcomes. The personalized sagittal reconstruction should be performed according to age difference for subaxial cervical spine surgery. Abstract : The age difference of cervical sagittal alignment was obvious, and the C2‐7 Cobb increased with age. The closer the correction of C2‐7 Cobb to the theoretical value, the smaller the loss of correction angle.